1985
DOI: 10.1038/316126a0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serotonin M-receptor subtypes and their specific blockade by a new class of drugs

Abstract: We describe a new class of drugs that selectively block serotonin M-receptors on peripheral neurones. Because of their high affinity, some of these drugs are the most potent of any pharmacological class yet reported. They have allowed the identification of three M-receptor subtypes, one of which is responsible for mediating the painful effects of serotonin in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
317
3
7

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 826 publications
(345 citation statements)
references
References 25 publications
17
317
3
7
Order By: Relevance
“…Furthermore, this result supports our suggestion that 5-HT2 receptors are predominantly involved in 5-HT-mediated mouse skin inflammation. It has been reported that 5-HT excites nociceptive sensory neurons, and application of 5-HT to a blister base gives rise to the sensation of pain (29). This activation of nociceptive neurons is mimicked by 2-methyl 5-HT, while the response to 5-HT is inhibited by ICS 205-930.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, this result supports our suggestion that 5-HT2 receptors are predominantly involved in 5-HT-mediated mouse skin inflammation. It has been reported that 5-HT excites nociceptive sensory neurons, and application of 5-HT to a blister base gives rise to the sensation of pain (29). This activation of nociceptive neurons is mimicked by 2-methyl 5-HT, while the response to 5-HT is inhibited by ICS 205-930.…”
Section: Discussionmentioning
confidence: 93%
“…Miner & Sanger, 1986. The recent synthesis of specific 5HT-3 receptor antagonists (Richardson et al, 1985) has led to the demonstration in animal models (Miner & Sanger, 1986) and in man (Cunningham et al, 1987;Leibungut & Lancranjan, 1987) of the importance of 5HT-3 receptor antagonism in anti-emesis.BRL43694 [Endo-N-(9-methyl-9-azabicyclo-(3,3, I)-non-3-yl)-I -methyl-indazole-3-carboxamide] has been recently developed by Beecham Pharmaceuticals Research Division as a selective 5HT-3 antagonist. In common with other agents of this class it rapidly abolishes vomiting induced by cisplatin in ferrets (Boyle et al, 1987 Table I.…”
mentioning
confidence: 99%
“…Miner & Sanger, 1986). The recent synthesis of specific 5HT-3 receptor antagonists (Richardson et al, 1985) has led to the demonstration in animal models (Miner & Sanger, 1986) and in man (Cunningham et al, 1987;Leibungut & Lancranjan, 1987) of the importance of 5HT-3 receptor antagonism in anti-emesis.…”
mentioning
confidence: 99%
“…Following the demonstration that metoclopramide was more effective at high doses (Gralla et al, 1981) and that high dose metoclopramide showed antagonism at the 5HT3 (or M) type receptor (Fozard, 1984) a new group of selective 5HT3 receptor antagonists, then recently developed (Brittain et al, 1987;Fake et al, 1987;Fozard, 1984;Richardson et al, 1985) were investigated as possible anti-emetics. Their effectiveness has surpassed other anti-emetic therapies in both animal models (Miner & Sanger, 1986;Miner, Sanger & Turner, 1987;Costall et al, 1986;Stables et al, 1987;Bermudez et al, 1988) and human studies (Cunningham et al, 1988;Liebundgut et at., 1988;Carmichael et al, 1988). So far they have only been employed singly and hence it was of interest to evaluate whether the effect of a 5HT3 receptor antagonist, GR38032F (Glaxo), against cyclophosphamideinduced vomiting in the ferret could be improved by combination with dexamethasone.…”
mentioning
confidence: 99%
“…The ferret is an animal that is well established for studies of emesis (Florczyck et al, 1982;Gylys & Gidda, 1986;King, 1988;Tuor et al, 1988) shows behavioural perturbations which may indicate nausea (Bermudez et al, 1987; and is a good predictive model of antiemetics for man (Miner et al, 1987). We employed a dose of GR38032F that had been established as effective in delaying but not reducing the emesis in this model (Stables et al, 1987) and observed whether this was influenced by dexamethasone. We also studied the effect of dexamethasone alone.…”
mentioning
confidence: 99%